2023
DOI: 10.1177/20503121221149536
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and sharp injuries and its associated factors among healthcare workers in Southern Ethiopia

Abstract: Background: Needlesticks and sharp injuries are occupational hazards for healthcare workers that result from the accidental piercing of the skin. Needlestick injuries expose healthcare workers to blood and body fluids that may be infected and can be transmitted to them. Healthcare workers have been exposed to blood-borne pathogens through contaminated needles and other sharp materials every day. Around 20 blood-borne diseases can be transmitted through casual needlesticks and sharp injuries. Objective: To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…All eligible articles were considered in the forest plot to determine the pooled prevalence of needlestick and sharp object injuries. Regarding the distributions of the included studies, the majority were conducted in the Amhara region ( 3 , 18 , 19 , 22 24 , 38 ), followed by Oromia ( 27 – 30 ), SNNPRs ( 15 , 16 , 31 ), Addis Ababa ( 25 , 26 ), and one each in Dire Dawa ( 33 ), Gambella ( 34 ), Sidama ( 35 ), Somali ( 36 ), and Tigray ( 32 ). All included studies used cross-sectional study designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All eligible articles were considered in the forest plot to determine the pooled prevalence of needlestick and sharp object injuries. Regarding the distributions of the included studies, the majority were conducted in the Amhara region ( 3 , 18 , 19 , 22 24 , 38 ), followed by Oromia ( 27 – 30 ), SNNPRs ( 15 , 16 , 31 ), Addis Ababa ( 25 , 26 ), and one each in Dire Dawa ( 33 ), Gambella ( 34 ), Sidama ( 35 ), Somali ( 36 ), and Tigray ( 32 ). All included studies used cross-sectional study designs.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate ranged from 82% (16) to 100% (17), with an average of 94.17%. Among the included original articles, eight studies were conducted in Amhara regional state (17)(18)(19)(20)(21)(22)(23)(24), two were conducted in the Addis Ababa city administration (25, 26), four studies each were conducted in the Oromia regional state (27)(28)(29)(30) and the South Nations, Nationalities, and Peoples' Region (SNNPR) (15,16,31), and one study each was conducted in the Tigray regional state (32), Dire Dawa (33), Gambella (34), Sidama (35), and Somali (36) (Table 1).…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Similarly, studies found that the older age groups of healthcare workers were more likely to be exposed to injuries compared to the younger age workers. 6 , 25 This could be because workers burn out and lose physical and cognitive abilities as they age, making it difficult for them to act correctly at work and putting them vulnerable to injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Night shift work may greatly increase the risk of HCWs sustaining NSSIs [ 19 ]. HCWs report high levels of job stress, burnout, and discontent, which increases their risk of sustaining NSSIs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%